The Implementation of Trias Politica Concept in The System of Government in Indonesian Constitution Post Amendment - Sahib, Agung (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
The purpose of this study is to identify the concept of implementing Trias Politika in the Unitary State Government System of the Republic of Indonesia. This can be seen in the Indonesian National Constitution of the Constitution of the Republic of Indonesia Year 1945, this research was conducted to analyze how the implementation of the political triad based on the 1945 Constitution, in addition, it was studied with case studies related to the material studied. an approach that is descriptive analysis by summarizing and describing the concept of Trias Politica in Indonesia, with library research methods sourced from books and lieratur. The results of this study show that the principle of checks and balances in the concept of trias politika is a constitutional principle that requires that legislative power, executive power and judicial power are balanced and supervise each other so that the power of state institutions can be regulated.